The Legal Rights of Drug Convicts: Stigma and Labelling in Judicial Practices - Putri Shandyana, Jullia; Adinda Putri, Sarah; Febriana, Nabilah (Ius Poenale, 2024)
Stigma against drug offenders often leads to systemic barriers, including limited access to legal representation, difficulties in obtaining quality rehabilitation services, and reduced opportunities for social reintegration. Certain legal policies further entrench this cycle of stigma, exacerbating social marginalization and undermining the efficacy of interventions aimed at addressing the consequences of drug use. This research aims to explore how labelling theory influences the legal treatment of drug offenders across different jurisdictions and to identify legal strategies that can mitigate stigma and social exclusion. The research finds that the protection of drug offenders' rights varies considerably between rehabilitation-focused and punitive legal approaches. These variations highlight the need for a human rights-based framework in crafting legal policies that promote inclusivity. Employing normative legal research methods, including statute and conceptual approaches, the analysis draws on primary legal materials (laws and official documents) and secondary sources (academic literature). The findings underscore critical challenges faced by drug offenders, including unfair treatment, privacy violations, and restricted access to rehabilitation services. Approaches based on negative labelling contribute to the reinforcement of marginalization, whereas rehabilitation-oriented models are more effective in facilitating social reintegration. This research offers valuable insights into the role of stigma in shaping the legal treatment of drug offenders and calls for the development of more inclusive, human rights-based, rehabilitation-focused legal policies to advance a fairer and more effective global criminal justice system.